2022
DOI: 10.1136/jnnp-2022-329124
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid β-synuclein as a synaptic biomarker for preclinical Alzheimer’s disease

Abstract: Introductionβ-synuclein (β-syn) is a presynaptic protein, whose cerebrospinal fluid (CSF) levels are increased in patients with Alzheimer’s diseases (AD) showing mild cognitive impairment (MCI) and dementia (dem). Here, we aimed to investigate CSF β-syn in subjects at different AD stages, including preclinical AD (pre-AD), and to compare its behaviour with another synaptic biomarker, α-synuclein (α-syn), and two biomarkers of neuro-axonal damage, namely neurofilament light chain protein (NfL) and total tau pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Our previous studies revealed a stage-independent association of CSF β-synuclein with AD because patients at the preclinical, MCI, and dementia stages showed similar elevated values. 11,15,17 CSF β-synuclein might be, thus, associated with the presence of AD pathology but not with clinical progression. Furthermore, the first results obtained in serum encourage investigations on β-synuclein as a peripheral biomarker of synaptic damage in AD and other neurodegenerative disorders, given the selective neuronal expression of the protein.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous studies revealed a stage-independent association of CSF β-synuclein with AD because patients at the preclinical, MCI, and dementia stages showed similar elevated values. 11,15,17 CSF β-synuclein might be, thus, associated with the presence of AD pathology but not with clinical progression. Furthermore, the first results obtained in serum encourage investigations on β-synuclein as a peripheral biomarker of synaptic damage in AD and other neurodegenerative disorders, given the selective neuronal expression of the protein.…”
Section: Discussionmentioning
confidence: 96%
“…Since there is evidence about the increase of CSF α-syn levels with disease duration 24 , 33 , the relatively low levels of α-syn found both in PD-MCI and in PD-CN in our series might be also due to the short disease duration of the patients included. CSF α-syn increase has been documented in other neurodegenerative disorders unrelated to α-syn pathology, namely AD 38 , Creutzfeldt–Jakob disease 39 and progressive supranuclear palsy 40 . Taken together, these findings indicate that CSF α-syn levels unspecifically reflect the ongoing synaptic damage, as already previously proposed 22 , 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to α-synuclein, our knowledge about the role of β-synuclein and γ-synuclein in cellular functions and pathology is somewhat limited. Recent findings about β-synuclein point to its role as an important biomarker for the early stages of Alzheimer’s disease (AD) [ 19 ]. The concentration of β-synuclein gradually increases in the cerebrospinal fluid beginning from the preclinical AD phase.…”
Section: Three Members Of the Synuclein Familymentioning
confidence: 99%
“…It may be considered a promising biomarker of synaptic damage in this disease. β-Synuclein may be used as a CSF biomarker for synaptic damage in AD; its level is elevated in both dementia and pre-dementia stages of AD [ 19 , 20 ]. Importantly, higher CSF α-synuclein levels are reported in pre-AD subjects but not in MCI-AD and dementia AD [ 19 ], pointing to its specificity as a biomarker.…”
Section: Three Members Of the Synuclein Familymentioning
confidence: 99%
See 1 more Smart Citation